UJI ANTAGONIS JAMUR TRICHODERMA, VERTICILLIUM DAN TORULOMYCES TERHADAP Ganoderma boninense Pat. SECARA IN VITRO - Zafitra, Zafitra; Elfina, Yetti; Ali, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of this research is to antagonistic assessment fungal Trichoderma, Verticillium and Torulomyces to Ganoderma boninense Pat. in vitro. This research has been conducted at Plant Pathology, Agriculture Faculty, University of Riau from March until May 2016. The research consisted of 2 steps as  follow : 1) Antagonistic assessment of Trichoderma, Verticillium and Torulomyces 2) measurement the diameter and growth antagonism fungus. Results of the research showed that Trichoderma had a better  inhibition  growth  to              G. boninense 81,21%, diameter of growth was 88,00 mm and colony growth 29,33 mm/day. The Endophytic Verticillium had inhibition growth 76,08%, diameter of growth  was  85,92 mm and colony growth 28,64 mm/day. The Torulomyces had inhibition growth 75,90%, diameter  of growth was 84,67 and colony growth 28,22 mm/day.  Keywords : Antagonistic Assessment, Ganoderma boninense, In vitro